Aboriginal Employment and Wages in Canada: A Decade of Positives and Negatives - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2017)
The employment and participation rates for Aboriginals improved in 2016 over 2015, while the unemployment rate remained the same. However, Aboriginals, as well as non-Aboriginals, have not reached the 2007 levels they were prior to the recession of 2008- 2009. Wages have improved annually and in most years at a rate greater than the consumer price index. This applies for Aboriginals and non-Aboriginals, except in 2016, when wages were basically unchanged for Aboriginals. In general, the rates of employment, unemployment, participation and wages are more favourable for non-Aboriginals than for Aboriginals. However, when examined by the level of education completed, employment rates are similar.Employment and wages are examined for the previous ten years, focusing on changes in 2007, which was prior to the recession, in 2010, immediately after the recession and in 2015 and 2016. Gender, age and educational differences are discussed.